2017
DOI: 10.3390/molecules22101804
|View full text |Cite
|
Sign up to set email alerts
|

Single Actin Bundle Rheology

Abstract: Bundled actin structures play an essential role in the mechanical response of the actin cytoskeleton in eukaryotic cells. Although responsible for crucial cellular processes, they are rarely investigated in comparison to single filaments and isotropic networks. Presenting a highly anisotropic structure, the determination of the mechanical properties of individual bundles was previously achieved through passive approaches observing bending deformations induced by thermal fluctuations. We present a new method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In addition to the apparent visual differences, the fluctuations of the formed bundles decreased with increasing sPX concentration as a direct result of their thicker, more tightly packed structure. [30,32]…”
mentioning
confidence: 99%
“…In addition to the apparent visual differences, the fluctuations of the formed bundles decreased with increasing sPX concentration as a direct result of their thicker, more tightly packed structure. [30,32]…”
mentioning
confidence: 99%
“…OT have been used to measure the bending stiffness of microtubules ( Kurachi et al, 1995 ; Felgner et al, 1996 ; van Mameren et al, 2009 ; Koch and Rohrbach, 2018 ; Memet et al, 2018 ), actin filaments ( van Mameren et al, 2009 ) and collagen fibrils ( Dutov et al, 2016 ). Other examples of mechanical properties of protein fibers measured with OT include torsional stiffness ( Tsuda et al, 1996 ; Yasuda et al, 1996 ), bending stiffness of fiber bundles ( Rückerl et al, 2017 ; Strehle et al, 2017 ), sliding forces of filaments within bundles ( Schnauß et al, 2016 ), and bending and spontaneous assembly of two interacting filaments using a four-trap OT instrument ( Kurniawan Nicholas et al, 2016 ). OT can also be used to measure the assembly and disassembly of individual protein filaments, as has been done for microtubules ( Dogterom et al, 2005 ; Rodríguez-García et al, 2020 ).…”
Section: Mechanics Of Higher-order Protein Fibers and Networkmentioning
confidence: 99%
“…Data points in all curves represent the mean of at least five independent measurements and error bars represent the standard deviation from the mean. To date, previous in vitro studies have investigated the mechanical properties of only one-component systems of either actin as entangled [33][34][35] and crosslinked [36][37][38][39][40] networks or keratin networks 24,25,30,31,41 and single filaments. 42 In our study, , composite networks of F-actin and K8-K18 with varying mixing ratios revealed an intermediate linear viscoelastic behavior with regard to their composite-specific protein content.…”
Section: Figmentioning
confidence: 99%